Profile of blood glucose and ultrastucture of beta cells pancreatic islet in alloxan compound induced rats - Suarsana, I Nyoman; Priosoeryanto, B.P; Bintang, M; Wresdiyati, T (Indonesian Journal of Animal and Veterinary Sciences, 2010)
Diabetes is marked by elevated levels of blood glucose, and progressive changes of the structure of pancreatic islet histopathology. The objective of this research was to analyse the glucose level and histophatological feature in pancreatic islet in alloxan compound induced rats. A total of ten male Spraque Dawley rats of 2 months old were used in this study. The rats were divided into two groups: (1) negative control group (K-), and (2) positif induced alloxan group (diabetic group =DM). The rats were induced by a single dose intraperitonial injection of alloxan compound 120 mg/kg of body weight. The treatment was conducted for 28 days. Blood glucose levels of rats were analysed at 0, 4, 7, 14, 21, and 28 days following treatment. At the end of the experiment, rats were sacrificed by cervical dislocation. Pancreas was collected for analysis of histopathological study by Immunohistochemical technique, and ultrastructural study using transmission electron microscope (TEM). The result showed that Langerhans islet of diabetic rat (rat of DM group) showed a marked reduction of size, number of Langerhans islet of diabetic rat decrease, and characterized by hyperglycemic condition. By using TEM, beta cells of DM group showed the rupture of mitochondrial membrane, the lost of cisternal structure of inner membrane of mitocondria, reduction of insulin secretory granules, linkage between cells acinar with free Langerhans islet, and the caryopicnotic of nucleus. Key words: Alloxan, Beta Cells, Rat, Blood Glucose, Immunohistochemistry